2018
DOI: 10.19082/6563
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diet on blood viscosity in healthy humans: a systematic review

Abstract: BackgroundIncreased whole blood viscosity is associated with increased risk of morbidity and mortality of several life-threatening diseases, including cardiovascular and cerebrovascular disease. The effect of diet on human health has been indicated in many studies, and a health dietary pattern can reduce the incidence of several chronic diseases.ObjectiveThe aim of this systematic review was to assess the effect of diet on blood viscosity and related parameters such as haematocrit (HCT).MethodsThis systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Studies supporting this hypothesis documented the relationship between hemorheological parameters and carotid or coronary artery atherosclerosis [20][21][22]. In addition, some studies have shown that increased WBV is associated with high morbidity and mortality in some settings, including vascular diseases 23. Inflammation is one of the key drivers of atheroscle-rotic plaque development.…”
mentioning
confidence: 90%
“…Studies supporting this hypothesis documented the relationship between hemorheological parameters and carotid or coronary artery atherosclerosis [20][21][22]. In addition, some studies have shown that increased WBV is associated with high morbidity and mortality in some settings, including vascular diseases 23. Inflammation is one of the key drivers of atheroscle-rotic plaque development.…”
mentioning
confidence: 90%
“…At low shear rates, blood cells aggregate, increasing viscosity, whereas the opposite happens at a high shear rate [ 1 - 3 ]. Increased whole blood viscosity (WBV) is associated with higher morbidity and mortality in some settings, including cardiovascular and cerebrovascular disease [ 2 ]. Blood viscosity is directly proportional to endothelial shear stress, which in turn is determined by vessel diameter, through the release of endothelial vasoactive factors [ 4 - 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…An understanding of coagulation begins with hemostasis and the hemostatic system. The circulation of blood with finely balanced viscosity is critical for healthy functioning [1]. In the case of injury, hemorrhaging must be limited, and the mechanism to ensure this is known as hemostasis [2].…”
Section: Hemostasis and The Hemostatic Systemmentioning
confidence: 99%